Microbioassay of Antimicrobial Agents - Simon, Harold J. (1970)
A previously described agar-diffusion technique for microbioassay of antimicrobial agents has been modified to increase sensitivity of the technique and to extend the range of antimicrobial agents to which it is applicable. This microtechnique requires only 0.02 ml of an unknown test sample for assay, and is capable of measuring minute concentrations of antibiotics in buffer, serum, and urine. In some cases, up to a 20-fold increase in sensitivity is gained relative to other published standardized methods and the error of this method is less than ±5%. Buffer standard curves have been established for this technique, concurrently with serum standard curves, yielding information on antimicrobial serum-binding and demonstrating linearity of the data points compared to the estimated regression line for the microconcentration ranges covered by this technique. This microassay technique is particularly well suited for pediatric research and for other investigations where sample volumes are small and quantitative accuracy is desired. Dilution of clinical samples to attain concentrations falling with the range of this assay makes the technique readily adaptable and suitable for general clinical pharmacological studies. The microassay technique has been standardized in buffer solutions and in normal human serum pools for the following antimicrobials: ampicillin, methicillin, penicillin G, oxacillin, cloxacillin, dicloxacillin, cephaloglycin, cephalexin, cephaloridine, cephalothin, erythromycin, rifamycin amino methyl piperazine, kanamycin, neomycin, streptomycin, colistin, polymyxin B, doxycycline, minocycline, oxytetracycline, tetracycline, and chloramphenicol.